ANTECEDENTS AND CONSEQUENCES OF INTENTION SUSTAINABLE CONSUMPTION BEHAVIOR WITH HEALTH CONSCIOUSNESS AS A MEDIATING VARIABLE - Robiansyah; Kurniawati (Tekmapro, 2025)
This study was conducted to analyze the effect of Social Responsibility Collectivism, External Incentives on Intention Sustainable Consumption Intention, the impact of Intention Sustainable Consumption on Sustainable Consumption Behaviour, and the effect of Sustainable Consumption Behaviour on Sustainable Intention both directly and moderated by Health Awareness. The research design used is quantitative research with causality hypothesis testing. The sample used is respondents who carry out sustainable consumption activities. The sampling technique used was purposive sampling, and the sample used was 385. The data analysis used is SEM using AMOS software. The research findings show that social responsibility and external incentives have been proven to positively affect the intention of sustainable consumption. While Collectivism is not proven to have a positive effect on Intention Sustainable Consumption, Intention Sustainable Consumption is proven to have a positive effect on Sustainable Consumption Behavior, and Sustainable Consumption Behavior has a positive effect on Continuous Intention, but Health Consciousness is not proven to moderate the positive impact of Sustainable Consumption Behavior on Continuous Intention. The results of this study provide information that sustainable consumption activities must pay attention to the behavior of consumers related to social responsibility, external incentives, sustainable consumption intentions, and sustainable consumption behavior.